Energy levels of even nuclei on the hydrodynamical model with vibration-rotation interaction - Klema, E. D.; Mallmann, C. A.; Day, P. (North Holland Publishing, 1961)
Fil: Klema, E. D. Comisión Nacional de Energía Atómica; Argentina